Exposure to E2 and EE2 environmental concentrations affect different components of the Brain-Pituitary-Gonadal axis in pejerrey fish (Odontesthes bonariensis) - Garriz, Angela (2017)
The present study focuses on the effects of E2 and EE2 environmental concentrations on different components of the reproductive axis of pejerrey (Odontesthes bonariensis), a native fish species from Pampas lakes of Argentina. The results obtained demonstrated that E2 and EE2 separate or mixed, could disrupt key pathways of the pejerrey Brain-Pituitary-Gonadal axis. First, it was observed that at the brain level, gnrh-III and cyp19a1b mRNA expression increased significantly in the exposed fish. Secondly, in the pituitary fshb and lhb mRNA expression levels, the study did not show any differences between treated and control groups. Thirdly, fshr and lhcgr transcript levels showed a significant decrease at testicular level. Nevertheless, testosterone plasmatic levels remained unchanged in exposed fish. In addition, in a histological analysis, it was possible to find pyknotic nuclei in estrogen only on treated fish testis linked to a reduction in the GSI index and a decrease in the length of spermatogenic lobules. All these findings highlighted the fact that environmental concentrations of E2, EE2 and their mixture disrupted the endocrine-reproductive axis of pejerrey, being the testis the main direct target.